MENDORONG DAN MENGARAHKAN PERILAKU SDM DALAM KEHIDUPAN ORGANISASI BISNIS Di ERA GLOBAL - Ardiana, I Dewa Ketut Raka (Program Doktor Ilmu Ekonomi, 2008)
Globalization provides opportunities and threats to individual as well as to the organization. In order to succeed, anticipation and readiness of everyone in the organization, both manager and employees, are very important. The opportunities may give a positive impact to all the aspects of the organization, including human resource aspect. Meanwhile, the problems may enhance competition also explosive environment, if the resources are not ready to face the challenge that might happened. To see this phenomenon depends on the attitude and policy from the organizationâ€™s leaders, to direct and push the human resources attitude so theyâ€™re able to see the changes that are happening.Â Key words: globalization, global competition, human resource behavior, global manager.